Annihilation of structural defects in chalcogenide absorber films for high-efficiency solar cells. Issue 5 (18th April 2016) - Mainz, Roland; Simsek Sanli, Ekin; Stange, Helena; Azulay, Doron; Brunken, Stephan; Greiner, Dieter; Hajaj, Shir; Heinemann, Marc D.; Kaufmann, Christian A.; Klaus, Manuela; Ramasse, Quentin M.; Rodriguez-Alvarez, Humberto; et al.
Abstract : Defects rapidly annihilate near stoichiometric composition. Abstract : In polycrystalline semiconductor absorbers for thin-film solar cells, structural defects may enhance electron–hole recombination and hence lower the resulting energy conversion efficiency. To be able to efficiently design and optimize fabrication processes that result in high-quality materials, knowledge of the nature of structural defects as well as their formation and annihilation during film growth is essential. Here we show that in co-evaporated Cu(In, Ga)Se2 absorber films the density of defects is strongly influenced by the reaction path and substrate temperature during film growth. A combination of high-resolution electron microscopy, atomic force microscopy, scanning tunneling microscopy, and X-ray diffraction shows that Cu(In, Ga)Se2 absorber films deposited at low temperature without a Cu-rich stage suffer from a high density of – partially electronically active – planar defects in the 112 planes. Real-time X-ray diffraction reveals that these faults are nearly completely annihilated during an intermediate Cu-rich process stage with [Cu]/([In] + [Ga]) > 1. Moreover, correlations between real-time diffraction and fluorescence analysis during Cu–Se deposition reveal that rapid defect annihilation starts shortly before the start of segregation of excess Cu–Se at the surface of the Cu(In, Ga)Se2 film. The presented results hence provide direct insights into the dynamics of the film-quality-improving mechanism.